Rare earth iron-based ring magnet and its manufacturing method

The method of mixing rare earth iron magnet powder with polystyrene and spark plasma sintering addresses the filling and productivity issues in rare earth iron magnet manufacturing, resulting in a magnet with enhanced mechanical strength and magnetic properties.

JP7621184B2Active Publication Date: 2025-01-24MINEBEAMITSUMI INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021086763
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-05-24
Publication Date
2025-01-24
Estimated Expiration
2041-05-24

AI Technical Summary

Technical Problem

The challenge of improving the filling property and productivity of rare earth iron magnet powder in manufacturing processes, particularly for ring magnets, while maintaining excellent mechanical strength and heat resistance, is addressed.

Method used

A method involving the use of magnetically isotropic rare earth iron magnet powder, mixed with polystyrene, forming a compound, and subjecting it to spark plasma sintering under controlled pressure and current density to create a rare earth iron ring magnet.

Benefits of technology

Enhances filling properties, improves productivity, and results in a rare earth iron ring magnet with superior mechanical strength and reduced carbon content, maintaining high coercive force and magnetic properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007621184000003
    Figure 0007621184000003
  • Figure 0007621184000004
    Figure 0007621184000004
  • Figure 0007621184000005
    Figure 0007621184000005
Patent Text Reader

Abstract

To provide a manufacturing method of a rare earth iron-based magnet capable of improving filling properties when filling rare earth iron-based magnet powder into a mold, improving productivity, and obtaining a rare earth iron-based magnet having excellent mechanical strength.SOLUTION: A manufacturing method of a rare earth iron ring magnet includes a step (a) of obtaining a rare earth iron magnet powder, a step (b) of making a compound, a step (c) of forming a green body, a step (d) of inserting the green body into a composite mold, setting the composite mold in a spark plasma sintering (SPS) device, applying pressure to the green body under reduced pressure, energizing the density, and degreasing the green body to obtain a degreased body, and a step (e) of applying a current density while applying pressure to the degreased body to sinter the degreased body to obtain a rare earth iron-based ring magnet.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a rare earth iron-based ring magnet and a method for producing the same. [Background technology]

[0002] Conventionally, with the miniaturization and high performance of devices, rare earth permanent magnets with high magnetic properties are used in a wide range of fields, such as rotating devices such as motors, general home appliances, audio devices, in-vehicle devices for automobiles, medical devices, and general industrial devices. As rare earth permanent magnets, there are magnets molded by mixing rare earth magnet powder with resin, so-called rare earth bonded magnets. Although this rare earth bonded magnet has a degree of freedom in molding, it has low heat resistance because it uses an organic material, resin, as a binder to bind the rare earth magnet powder, and it may be difficult to use it in in-vehicle devices that are exposed to high temperature environments.

[0003] In response to this, a method has been proposed for producing rare earth iron-based permanent magnets in which rare earth magnetic powders are bonded together by spark plasma sintering (SPS) without using resin, which is an organic material (see, for example, Patent Documents 1 and 2).

[0004] In the manufacturing method of rare earth iron-based permanent magnets of Patent Documents 1 and 2, first, ultra-quenched rare earth iron-based flakes obtained by crushing a ribbon containing 13 to 15 atomic % rare earth elements, 0 to 20 atomic % Co, 4 to 11 atomic % B, and the remainder Fe and unavoidable impurities are filled into a cavity. Next, the assembly of ultra-quenched rare earth iron-based flakes is compressed at a predetermined pressure under a predetermined reduced pressure and discharge plasma sintered. In this way, the rare earth iron-based flakes can be bonded together without using resin to obtain a rare earth iron-based permanent magnet. The rare earth iron-based permanent magnets obtained by the manufacturing methods of Patent Documents 1 and 2 have the advantage of being more heat resistant than rare earth bonded magnets because they do not use resin, which is an organic material, as a binder. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. Hei 2-198104 [Patent Document 2] Japanese Patent Application Publication No. 3-284809 Summary of the Invention [Problem to be solved by the invention]

[0006] However, the rare earth iron-based magnet powder obtained by pulverizing the thin ribbon produced by the ultra-rapid cooling method has a flat shape, which poses the problem of low fluidity and filling ability when filling the rare earth iron-based magnet powder into a cavity.

[0007] Therefore, an object of the present invention is to provide a method for manufacturing a rare earth iron-based ring magnet that improves the filling properties when filling a mold with rare earth iron-based magnet powder, improves productivity, and produces a rare earth iron-based ring magnet with excellent mechanical strength. [Means for solving the problem]

[0008] In order to solve the above problems and achieve the object, a method for producing a rare earth iron-based ring magnet according to one embodiment of the present invention includes the steps of: (a) pulverizing a magnetically isotropic rare earth iron-based magnet ribbon produced by a rapid cooling method to obtain a rare earth iron-based magnet powder; (b) mixing the rare earth iron-based magnet powder with polystyrene to produce a compound; (c) filling a die with the compound and applying pressure thereto to form a green body; and (d) inserting the green body into a composite die, setting the composite die in a spark plasma sintering (SPS) device, and then sintering the green body under reduced pressure at a pressure of 5 MPa to 15 MPa while applying a current of 250 A / cm. 2 More than 550A / cm 2 (e) applying a pressure of 15 MPa to 200 MPa to the degreased body under reduced pressure while heating the green body at a current density of less than 550 A / cm 2 More than 1050A / cm 2and heating the degreased body by passing an electric current at a current density below to sinter the degreased body to obtain a rare earth iron-based ring magnet, wherein the rare earth iron-based magnet powder contains rare earth elements in an amount of 13 at % or more and 19 at % or less. Effect of the Invention

[0009] According to one aspect of the present invention, the filling properties when filling a die with rare earth iron-based magnetic powder are improved, improving productivity, and a rare earth iron-based ring magnet with excellent mechanical strength can be obtained. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a diagram specifically illustrating the method for producing a rare earth iron-based ring magnet according to an embodiment. [Diagram 2] FIG. 2 is a diagram showing the measurement results of the radial crushing strength of Samples 1 and 2. [Diagram 3] FIG. 3 is a diagram showing the measurement results of the radial crushing strength of Samples 1, 3, and 4. [Figure 4] FIG. 4 is a diagram showing the measurement results of the initial demagnetization rates of Samples 1, 3, and 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings. Note that the present invention is not limited to this embodiment. In addition, the components in the following embodiments include those that are replaceable and easy for a person skilled in the art, or those that are substantially the same.

[0012] <Method of manufacturing rare earth iron-based ring magnet according to the embodiment> The method for producing a rare earth iron-based ring magnet according to the embodiment includes steps (a) to (e) described below. It may further include step (f). Figure 1 is a diagram for specifically explaining the method for producing a rare earth iron-based ring magnet according to the embodiment.

[0013] In step (a), the magnetically isotropic rare earth iron-based magnet ribbon produced by the rapid cooling method is pulverized to obtain rare earth iron-based magnet powder. Usually, the rare earth iron-based magnet ribbon is pulverized and then classified to obtain rare earth iron-based magnet powder. The rare earth iron-based magnet powder produced by the rapid cooling method is usually flat, and is preferably classified into a range of 53 μm to 150 μm. The obtained rare earth iron-based magnet powder is also magnetically isotropic. The rare earth iron-based magnet powder preferably contains at least Nd as a rare earth element, and is, for example, an Nd-Fe-B magnet. An Nd-Fe-B magnet is a ternary tetragonal compound Nd 2 Fe 14It contains a B-type compound phase as the main phase. In addition, Nd-Fe-B magnets usually further contain a rare earth rich phase (Nd rich phase) and the like. Nd-Fe-B magnets may be used alone or in combination of two or more. Rare earth iron magnet powder (specifically, Nd-Fe-B magnets) may contain rare earth elements other than Nd. Examples of rare earth elements other than Nd include praseodymium (Pr), scandium (Sc), yttrium (Y), lanthanum (La), cerium (Ce), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), and lutetium (Lu). The rare earth elements other than Nd may be used alone or in combination of two or more. In the Nd-Fe-B magnet, Fe may be partially (usually less than 50 atomic %) replaced with Co. The Nd-Fe-B magnet may also contain other elements. Examples of the other elements include titanium (Ti), zirconium (Zr), niobium (Nb), molybdenum (Mo), hafnium (Hf), tantalum (Ta), tungsten (W), copper (Cu), and gallium (Ga). The other elements may be used alone or in combination of two or more. The rare earth iron magnet powder contains rare earth elements in an amount of 13 at% or more and 19 at% or less. The amount of rare earth elements increases with the amount of rare earth rich phase. In the manufacturing method of the rare earth iron ring magnet according to the embodiment, a small amount of carbon derived from the polystyrene mixed in step (b) may remain in the obtained rare earth iron ring magnet. However, because rare earth iron magnet powder containing a large amount of rare earth-rich phase is used, the deterioration of magnetic properties caused by the residual carbon can be suppressed. Specifically, the greater the amount of rare earth element, the higher the original coercivity can be, so that even if the coercivity is somewhat reduced by the residual carbon, sufficient coercivity can be maintained. Similarly, the greater the amount of rare earth element, the less the influence of the residual carbon on the initial demagnetization and squareness ratio can be. However, if the amount of rare earth element exceeds 19 at%, the magnetization may decrease too much, or the coercivity may become too large, resulting in a decrease in magnetizability.On the other hand, if the amount of rare earth elements is less than 13 at%, the magnetic properties may deteriorate during sintering. Also, the deterioration of the magnetic properties caused by the residual carbon may not be sufficiently suppressed. The rare earth iron-based magnet powder preferably has a coercive force of 1500 kA / m or more.

[0014] In step (b), the rare earth iron-based magnet powder is mixed with polystyrene to prepare a compound. Since polystyrene does not contain oxygen atoms, it is difficult to deteriorate the magnetic properties of the obtained rare earth iron-based ring magnet. In step (b), specifically, polystyrene is dissolved in an organic solvent to prepare a resin solution. Here, the organic solvent may be a solvent that can dissolve polystyrene and can evaporate during drying, which will be described later. As the organic solvent, methyl ethyl ketone is preferably used. The rare earth iron-based magnet powder and this resin solution are kneaded. Next, the kneaded mixture obtained by kneading is dried, and the organic solvent is evaporated, and then the mixture is crushed. The crushed product obtained by crushing is classified to obtain a compound. In step (b), polystyrene is preferably mixed in an amount of 2 wt% or less relative to 100 wt% of the rare earth iron-based magnet powder, and more preferably mixed in an amount of 1 wt% to 2 wt%. If the amount exceeds 2 wt%, carbide is generated in step (e), the amount of remaining carbon in the rare earth iron ring magnet increases, and the magnetic properties may be excessively deteriorated. If the amount is less than 1 wt%, the improvement of the packing property in step (c) may be insufficient. The compound is preferably classified into a range of 125 μm or less. It is more preferable that the compound is classified into a range of 20 μm or more and 125 μm or less. Classification into the above range can further improve the packing property in step (c). The mechanical strength of the obtained rare earth iron ring magnet can also be improved.

[0015] In step (c), the compound is filled into a mold and pressed to form a green body. The compound has a higher fluidity than the magnet powder used to prepare the compound. Therefore, the compound is quickly filled into the mold. In other words, compounding improves the filling property. Since the filling time can be shortened, the productivity of rare earth iron ring magnets can also be improved. Furthermore, damage to the mold caused by the magnetic powder can be suppressed. During the compression molding in step (c), it is preferable to apply a pressure of 200 MPa or more and 1000 MPa or less to the mold containing the compound. This allows a green body in which the particles of the compound are in close contact with each other to be obtained. In addition, the compression molding in step (c) is usually performed at room temperature. The mold may be made of a material that can withstand the above pressure range. Note that the composite mold used in steps (d) and (e) is for spark plasma sintering (SPS), so there is a concern that it may be deformed or damaged if the pressure is not lower than the above pressure range. The shape and size of the mold can be appropriately determined in consideration of the shape and size of the rare earth iron-based ring magnet to be finally produced, so that a molded body of a preferred shape (ring-like) and size can be obtained. For example, if the dimensions and weight of the molded body are determined from the specifications of the finished product, a processing-less process can be achieved. In other words, a rare earth iron-based ring magnet can be produced by net-shape molding. In addition, it is preferable that the size of the molded body obtained in step (c) is slightly smaller than the dimensions of the composite mold used in steps (d) and (e). This has the advantage of making it easier to put into the composite mold. When a thin rare earth iron-based ring magnet, for example, with a thickness of 0.8 mm to 2.5 mm, is ultimately produced, it is necessary to thinly fill the mold with the compound in step (c). Even in this case, in this embodiment, the compound is compounded in advance, so the filling property is excellent. On the other hand, if the magnet powder is used alone, it is necessary to fill it more carefully and over a longer period of time, which is cumbersome.

[0016] In step (d), the green body is inserted into a composite die, and the composite die is set in a spark plasma sintering (SPS) device. Next, under reduced pressure, a pressure of 5 MPa to 15 MPa is applied to the green body, while a current of 250 A / cm is applied. 2 More than 550A / cm2 The green body is degreased by passing a current at a current density of less than 1000 rpm to obtain a degreased body. Specifically, an ON-OFF DC pulse current is passed through the green body.

[0017] As the composite die, a composite die (warm forming die) made of a combination of ceramics and cemented carbide is preferably used. -3 Pa or more 10 1 It is preferable to carry out the degreasing under a reduced pressure of 100 Pa or less. It is also preferable to apply a pressure in the above range to the green body in order to pass an electric current. Furthermore, when an electric current is passed through the green body at a current density in the above range, the green body can be heated from room temperature to a temperature at which polystyrene decomposes (specifically, a temperature of 350° C. or more and 400° C. or less), and degreasing can be carried out suitably.

[0018] In step (e), a pressure of 15 MPa to 200 MPa is applied to the degreased body under reduced pressure, and a current of 550 A / cm 2 More than 1050A / cm 2 The degreased body is heated by passing current at the following current density, and sintered to obtain a rare earth iron ring magnet (bulk body). Step (e) can be performed directly after step (d) using a spark plasma sintering (SPS) device. Specifically, ON-OFF DC pulse current is then passed through the degreased body.

[0019] The heating for the sintering was 10 -3 Pa or more 10 1It is preferable to carry out the sintering under a reduced pressure of 10 Pa or less. In addition, in order to efficiently densify the degreased body, it is preferable to apply a pressure in the above range to the degreased body. Furthermore, when the degreased body is energized with a current density in the above range, the degreased body can be heated from the temperature during degreasing to a temperature at which sintering proceeds (specifically, the ultimate temperature at which the Nd-Fe-B magnet can form a liquid phase, for example, the ultimate temperature of 600°C to 750°C), and sintering can be carried out suitably. In order to suppress the growth of crystal grains, it is preferable to end the sintering by limiting the holding time at the ultimate temperature to 5 minutes or less. Furthermore, it is more preferable to end the sintering without holding the heating temperature when the rate of change becomes 0. Here, the rate of change is the time derivative of the displacement during sintering (such as the distance moved by the punch).

[0020] In this embodiment, since the degreasing and spark plasma sintering (SPS) are performed after the molded body is formed in advance, the magnetic powder can be easily filled into the composite mold. In addition, since the degreasing and spark plasma sintering (SPS) are performed after the molded body is formed in advance, the heating efficiency is improved, the sintering time can be shortened, and the sintering temperature can be lowered. As a result, the deterioration of magnetic properties such as coercivity and squareness can be suppressed in the obtained rare earth iron-based ring magnet. In addition, if the magnet powder is used in its original state and the spark plasma sintering (SPS) is performed as in the conventional method, an irregular current path may be generated due to the density of the magnet powder. This may cause localized coarse grains, and the magnetic properties may vary, such as a decrease in initial demagnetization. In contrast, in this embodiment, since the degreasing and spark plasma sintering (SPS) are performed after the molded body is formed in advance, the magnetic properties are less likely to vary and the quality can be improved. In addition, since the degreasing and spark plasma sintering (SPS) are performed after the molded body is formed in advance, the height of the mold and the height inside the sintering device chamber can be minimized. Furthermore, in this embodiment, the rare earth iron-based ring magnet can be easily demolded. This is also true for rare earth iron-based ring magnets with a thin thickness. This is thought to be because the carbon that is removed from the green body during degreasing in step (d) plays the role of a release agent. In addition, the composite mold may be subjected to a demolding treatment before inserting the green body, but since demolding is easy as described above, the amount of release agent can be reduced. In addition, since demolding is easy as described above, the mold is less likely to become dirty, the cleaning effort is reduced, and as a result, the mold life is improved. In addition, since the green body is ring-shaped, carbon is more easily removed during degreasing than in a cylindrical shape, and the amount of remaining carbon in the rare earth iron-based ring magnet can be reduced.

[0021] In this embodiment, by carrying out densification after degreasing, the carbon content in the rare earth iron ring magnet can be sufficiently reduced, which is believed to improve the mechanical strength.

[0022] The rare earth iron-based ring magnet obtained in step (e) is cooled to normal room temperature or to a temperature range where it can be removed. The cooling may be performed while applying pressure, or may be performed under atmospheric pressure or reduced pressure using an inert gas, but is preferably performed as described below. That is, the manufacturing method of the rare earth iron-based ring magnet according to the embodiment preferably further includes step (f) of cooling the rare earth iron-based ring magnet while gradually reducing the pressure and the current density applied to the rare earth iron-based ring magnet obtained by sintering in step (e) in an inert gas atmosphere. Here, "gradually reducing" the pressure includes cases where it is reduced continuously and cases where it is reduced stepwise. Also, "gradually reducing" the current density includes cases where it is reduced continuously and cases where it is reduced stepwise. After that, the rare earth iron-based ring magnet is removed from the mold after it has reached normal room temperature or a temperature range where it can be removed.

[0023] The inert gas atmosphere is N 2 Examples of suitable atmospheres include an inert gas atmosphere and an Ar gas atmosphere. Specifically, cooling can be performed while flowing an inert gas inside and outside the mold, thereby shortening the cooling time. It is also preferable to gradually reduce the pressure applied in step (e) until it reaches 0 MPa, for example, over a period of 3 to 5 minutes. It is also preferable to gradually reduce the current density applied in step (e) until it reaches 0 A / cm. 2 It is preferable to gradually reduce the temperature over a period of, for example, 3 to 5 minutes until the temperature reaches 100° C. Gradual cooling in an inert gas atmosphere can suppress the growth of crystal grains in the magnet powder due to thermal history in the high temperature region, and also suppress oxidation. As a result, the magnetic properties can be improved.

[0024] Furthermore, a magnetization step may be carried out to magnetize the obtained rare earth iron-based ring magnet. The magnetization step may be carried out by a known method. If necessary, a surface treatment step may be carried out to perform a surface treatment (anti-rust treatment) on the obtained rare earth iron-based ring magnet, and then a magnetization step may be carried out to magnetize the surface-treated rare earth iron-based ring magnet. In the surface treatment step, surface treatments such as plating with nickel (Ni), tin (Sn), zinc (Zn), etc., aluminum (Al) vapor deposition, and resin coating are carried out.

[0025] Furthermore, the step (b) may be a step of preparing a compound by mixing the rare earth iron-based magnet powder, polystyrene, and further a lubricant. Specifically, in the step (b), the lubricant may be mixed in an amount of 0.2 wt% or less relative to a total of 100 wt% of the rare earth iron-based magnet powder and polystyrene. Moreover, it is more preferable to mix the lubricant in an amount of 0.05 wt% or more and 0.2 wt% or less relative to a total of 100 wt% of the rare earth iron-based magnet powder and polystyrene. Using a lubricant can further improve the packing property in the step (c). If the amount exceeds 0.2 wt%, carbide is generated in the step (e), and the amount of remaining carbon in the rare earth iron-based ring magnet increases, which may cause a decrease in magnetic properties and a decrease in strength. If the amount is less than 0.05 wt%, the further improvement in packing property in the step (c) may be insufficient.

[0026] Specifically, a lubricant is mixed after classification in step (b) of Fig. 1. That is, a lubricant is further mixed into the classified compound. In this case, in step (c), the compound mixed with the lubricant is filled into a mold and pressurized to form a green body. Calcium stearate is preferably used as the lubricant.

[0027] <Rare earth iron-based ring magnet according to the embodiment> The rare earth iron-based ring magnet according to the embodiment is a rare earth iron-based ring magnet obtained by spark plasma sintering rare earth iron-based magnet powder, the rare earth iron-based magnet powder being a magnetically isotropic ultra-quenched powder, containing rare earth elements in an amount of 13 at% to 19 at% and having a coercive force of 1500 kA / m or more. The rare earth iron-based ring magnet also has a radial crushing strength of 100 MPa or more and an initial demagnetization rate of less than 10%. Preferably, the rare earth iron-based ring magnet has a carbon content of 2000 ppm or less and an average crystal grain size of less than 200 nm. Here, the average crystal grain size is the average value of the individual crystal grain sizes obtained from the images of the magnet structure observed by SEM or TEM.

[0028] The rare earth iron based magnetic powder preferably contains at least Nd as the rare earth element, for example. Details of the rare earth iron based magnetic powder are the same as those described in the method for producing a rare earth iron based ring magnet according to the embodiment.

[0029] The rare earth iron-based ring magnet according to the embodiment has excellent magnetic properties and mechanical strength because the carbon content is suppressed.

[0030] The rare earth iron ring magnet according to the embodiment may be thin, for example, in the range of 0.8 mm to 2.5 mm. The thinner it is, the easier it is to degrease. The outer diameter is, for example, in the range of 10 mm to 50 mm. The rare earth iron ring magnet according to the embodiment has a coercive force of, for example, 1200 kA / m to 1800 kA / m.

[0031] Such a rare earth iron-based ring magnet can be obtained, for example, by the method for manufacturing a rare earth iron-based ring magnet according to the embodiment described above.

[0032] Incidentally, JP 2013-191612 A proposes a manufacturing method for obtaining a rare earth permanent magnet by mixing pulverized magnet powder with a binder to produce a compound, forming the produced compound into a sheet shape to produce a green sheet, subjecting this green sheet to a calcination treatment at a binder decomposition temperature, and subsequently subjecting the green sheet to spark plasma sintering (SPS).

[0033] The rare earth permanent magnet of JP2013-191612A is an anisotropic magnet powder of Nd-Fe-B system, which is composed of 27-40wt% Nd, 0.8-2wt% B, and 60-70wt% Fe. Then, a binder is mixed with the magnet powder to prepare a compound. The amount of binder added is 1wt%-40wt%, more preferably 2wt%-30wt%, and even more preferably 3wt%-20wt% relative to the total amount of the magnet powder and the binder. Next, the compound is molded into a sheet to form a green sheet, and the green sheet is heated to a temperature equal to or higher than the glass transition point or melting point of the binder to soften the green sheet. A magnetic field is applied to perform magnetic field orientation, and the magnetization easy axis of the magnet contained in the green sheet is oriented in a predetermined direction. Then, the magnetically oriented green sheet is punched into a desired shape to form a compact. The compact is then calcined in a non-oxidizing atmosphere (e.g., a hydrogen atmosphere or a mixed gas atmosphere of hydrogen and an inert gas) to decompose the binder and degrease it.The calcined compact is then subjected to spark plasma sintering (SPS) to obtain a rare earth permanent magnet.

[0034] The method of manufacturing rare earth permanent magnets in JP 2013-191612 A involves magnetic field orientation of the molded green sheet to orient the magnetization easy axis of the magnet contained in the green sheet in a specific direction, so the binder ratio is high (more preferably 3wt% to 20wt%). For this reason, the degreasing process to break down the binder takes time.

[0035] The magnetically oriented green sheet is punched into a desired shape to form a compact, which is then calcined in a non-oxidizing atmosphere (e.g., a hydrogen atmosphere or a mixed gas atmosphere of hydrogen and an inert gas) to decompose the binder and degrease the compact. However, this must be done in a hydrogen atmosphere or a mixed gas atmosphere of hydrogen and an inert gas, and such calcination using hydrogen requires sufficient safety precautions and equipment.

[0036] The magnetic powder in JP 2013-191612 A is an anisotropic magnet, and an ingot of a magnet alloy is roughly pulverized by a stamp mill, a crusher, or the like. Alternatively, the ingot is melted, flakes are produced by a strip casting method, and the roughly pulverized magnet powder is obtained by a hydrogen crushing method. In contrast, in this embodiment, the magnetic powder is a magnetically isotropic super-quenched powder produced by a super-quenching method, and the average crystal grain size of both magnets produced by spark plasma sintering (SPS) is different. The magnetic powder in JP 2013-191612 A is produced by melting an ingot and producing flakes by a strip casting method, and therefore the cooling rate is slower than that of the super-quenched powder, and therefore the average crystal grain size of the magnetic powder is larger, and as a result, the average crystal grain size of the magnet produced by spark plasma sintering (SPS) is also larger.

[0037] Furthermore, the present invention is not limited to the above-mentioned embodiment. The present invention also includes configurations in which the above-mentioned components are appropriately combined. Further effects and modifications can be easily derived by those skilled in the art. Therefore, the broader aspects of the present invention are not limited to the above-mentioned embodiment, and various modifications are possible.

[0038] [Example] [Experimental Example 1] The molded green body was inserted into a mold and the debinding and sintering processes were carried out successively. The effect of the debinding process was evaluated based on samples 1 and 2.

[0039] [Sample 1] Using a free pulverizer (Model M-2, manufactured by Nara Machinery Co., Ltd.), Nd-Fe-B magnet powder (rare earth element content: 13.8 at%, coercivity: 1500 kA / m or more, ultra-quenched powder) was pulverized and classified into the range of 53 μm to 150 μm. 4 g of polystyrene previously dissolved in 20 g of methyl ethyl ketone (MEK) was added to 200 g of the classified magnet powder, and the mixture was kneaded for 15 minutes in a laboratory mill while evacuating the air in a draft chamber to obtain a kneaded mixture. The kneaded product was placed in an oven heated to 80° C. and dried for 30 minutes to volatilize the MEK. The powder from which the MEK had been volatilized was crushed in a mortar and classified into particles of 20 μm to 125 μm or less using a dry sieve to obtain a compound. Next, the compound was filled into a ring-shaped mold having an outer diameter of 13 mm and an inner diameter of 11 mm, and powder compression molding was performed by applying a pressure of 300 MPa to mold a ring-shaped green body. The green body was inserted into a composite mold made of ceramics and cemented carbide, and then heated for 10 min in a spark plasma sintering (SPS) device using a rotary pump. -3 The degreasing was carried out under reduced pressure while drawing a vacuum to about Torr. Specifically, a pressure of 10 MPa was applied and a current of 400 A / cm was applied. 2 A current density of 1000 μm was applied and held for a predetermined time to perform degreasing. Subsequently, a pressure of 120 MPa was applied, and 800 A / cm 2 The sintering was carried out continuously by applying a current density of 1000 Hz and heating the mixture to about 700°C. After sintering is complete, the pressure and current are immediately shut off and N is pumped into the chamber. 2 Gas was introduced and the mixture was cooled under atmospheric pressure (immediately after sintering, the pressure was reduced to 0 MPa and the current density to 0 A / cm). 2 As the chamber is filled with N 2 Gas was introduced and cooling was carried out under atmospheric pressure.) After cooling to the specified temperature, the magnet was demolded to obtain a rare earth iron ring magnet. Four samples of Sample 1, No. 1 to No. 4, were prepared.

[0040] [Sample 2] In the same manner as in sample 1, a ring-shaped green body was molded. The green body was inserted into a composite mold made of ceramics and cemented carbide, and then heated for 10 min in a spark plasma sintering (SPS) device using a rotary pump. -3 The vacuum was drawn down to about Torr, and pulse current sintering was performed under reduced pressure. Specifically, a pressure of 120 MPa was applied, and a current of 800 A / cm was applied. 2 The debinding and sintering were carried out successively by applying a current density of 1000 Hz and heating the material from room temperature to around 700°C. After sintering is complete, the current is cut off and N 2 Gas was introduced and the mixture was cooled under atmospheric pressure (immediately after sintering, the pressure was reduced to 0 MPa and the current density to 0 A / cm). 2 As the chamber is filled with N 2 Gas was introduced and cooling was carried out under atmospheric pressure.) After cooling to the specified temperature, the magnet was demolded to obtain a rare earth iron ring magnet. Four pieces of Sample 2, No. 1 to No. 4, were prepared.

[0041] Table 1 shows the measurement results of the radial crushing strength of samples 1 and 2. FIG. 2 shows the measurement results of the radial crushing strength of samples 1 and 2. As shown in FIG. 2, the radial crushing strength of sample 2 is lower than that of sample 1. From this result of radial crushing strength, it is presumed that the degreasing stage was insufficient in sample 2, so binder residue remained inside, resulting in reduced mechanical strength.

[0042] [Table 1]

[0043] [Experimental Example 2] From the results of the debinding effect in Experimental Example 1, it is understood that the radial crushing strength can be improved by performing debinding under the conditions of Sample 1. For this reason, when the debinding process and sintering process of Sample 1 were performed, the relationship between the conditions in the cooling process after sintering and the initial demagnetization was investigated.

[0044] [Sample 3] The sintering process was carried out in the same manner as for sample 1. After sintering is complete, fill the chamber with N 2Gas was introduced and the current density was reduced to 0 A / cm over a period of approximately 180 seconds at atmospheric pressure without immediately interrupting the current. 2 The temperature was gradually reduced to 120 MPa, and the pressure was also gradually reduced from 120 MPa to 0 MPa for cooling. After cooling to a predetermined temperature, the magnet was demolded to obtain a rare earth iron ring magnet. Four pieces of Sample 3, No. 1 to No. 4, were prepared.

[0045] [Sample 4] The sintering process was carried out in the same manner as for sample 1. After sintering, the inside and outside of the composite mold were 2 While the gas was flowing, the current density was reduced to 0 A / cm over a period of approximately 180 seconds without immediately interrupting the current. 2 The temperature was gradually reduced to 120 MPa, and the pressure was also gradually reduced from 120 MPa to 0 MPa for cooling. After cooling to a predetermined temperature, the magnet was demolded to obtain a rare earth iron ring magnet. Four samples of Sample 4, No. 1 to No. 4, were prepared.

[0046] Table 2 shows the results of measuring the radial crushing strength and initial demagnetization rate of samples 1, 3, and 4. FIG. 3 shows the results of measuring the radial crushing strength of samples 1, 3, and 4. FIG. 4 shows the results of measuring the initial demagnetization rate of samples 1, 3, and 4. As shown in FIG. 3, the radial crushing strength of samples 3 and 4 is higher than that of sample 1. From the results of the radial crushing strength, it can be seen that in the cooling process after sintering, the current application is not immediately cut off after sintering, but the applied current is gradually reduced for a certain period of time, thereby suppressing the decrease in radial crushing strength. This is presumably because, when the applied current is cut off immediately after sintering, the mold temperature drops sharply, causing distortion in the sintered object due to thermal shock and temperature distribution.

[0047] On the other hand, looking at the initial demagnetization rate, the radial crushing strengths of samples 3 and 4 are almost the same, but the initial demagnetization rate of sample 4 is significantly smaller than that of sample 3. For sample 3, the applied current was gradually reduced after sintering, but unlike sample 4, the N 2Because no gas was flowing, it is presumed that, although it was only for a short time, the crystal grains of the magnetic powder grew due to their history in the high temperature region, resulting in a decrease in coercivity. Sample 4 shows that it is possible to obtain a rare earth iron-based ring magnet with high radial crushing strength and small initial demagnetization rate.

[0048] [Table 2]

[0049] [Evaluation of mechanical strength and magnetic properties] For mechanical strength, radial crushing strength was measured according to JIS Z2507. For magnetic properties, initial demagnetization rate was measured. The initial demagnetization rate was evaluated by exposing the obtained rare earth iron ring magnet to high temperature (200°C, 1 hour), then measuring the magnetic flux density at room temperature, and determining the rate of change before and after heat exposure.

[0050] [Carbon content, average crystal grain size] The carbon content and average crystal grain size were measured for the rare earth iron ring magnets (samples 1 to 4) obtained in the examples. The carbon content of each rare earth iron ring magnet was 2000 ppm or less, and the average crystal grain size was less than 200 nm. The carbon content was measured by a combustion method using a CS analyzer.

Claims

1. A rare earth iron-based ring magnet obtained by spark plasma sintering rare earth iron-based magnet powder, The rare earth iron-based magnet powder is a magnetically isotropic super-quenched powder, contains rare earth elements in an amount of 13 at% or more and 19 at% or less, and has a coercive force of 1500 kA / m or more; The rare earth iron-based ring magnet has a radial crushing strength of 100 MPa or more and an initial demagnetization rate of less than 10%. Rare earth iron ring magnet.

2. The rare earth iron-based ring magnet has a carbon content of 2000 ppm or less and an average crystal grain size of less than 200 nm. The rare earth iron-based ring magnet according to claim 1 .

3. The rare earth iron-based magnet powder contains at least Nd as the rare earth element.

3. The rare earth iron-based ring magnet according to claim 1 or 2.

4. (a) pulverizing a magnetically isotropic rare earth iron-based magnet ribbon produced by a rapid cooling method to obtain rare earth iron-based magnet powder; (b) mixing the rare earth iron-based magnet powder with polystyrene to prepare a compound, and classifying the compound into a range of 20 μm to 125 μm; (c) filling a mold with the compound and applying pressure to form a green body; (d) The green body is inserted into a composite die, and the composite die is set in a spark plasma sintering (SPS) device. Then, under reduced pressure, a pressure of 5 MPa to 15 MPa is applied to the green body while a pressure of 250 A / cm is applied. 2 More than 550A / cm 2 and heating the green body by passing a current at a current density of less than 1000 nm to degrease the green body to obtain a degreased body. (e) Under reduced pressure, a pressure of 15 MPa to 200 MPa is applied to the degreased body, and a pressure of 550 A / cm 2 More than 1050A / cm 2 and heating the degreased body by passing an electric current through the degreased body at a current density below to obtain a rare earth iron-based ring magnet. The rare earth iron-based magnet powder contains rare earth elements in an amount of 13 at % or more and 19 at % or less. A manufacturing method for rare earth iron-based ring magnets.

5. Furthermore, the method includes a step of (f) cooling the rare earth iron-based ring magnet obtained by sintering in an inert gas atmosphere while gradually reducing the pressure applied to the rare earth iron-based ring magnet and the current density applied thereto. A method for producing the rare earth iron-based ring magnet according to claim 4.

6. The rare earth iron-based magnet powder contains at least Nd as the rare earth element. A method for producing the rare earth iron-based ring magnet according to claim 4 or 5.

7. In the step (b), the polystyrene is mixed in an amount of 2 wt % or less with respect to 100 wt % of the rare earth iron-based magnet powder. The method for producing the rare earth iron-based ring magnet according to any one of claims 4 to 6.

8. The step (b) is a step of preparing a compound by mixing the rare earth iron-based magnet powder, the polystyrene, and a lubricant, In the step (b), the lubricant is mixed in an amount of 0.2 wt % or less with respect to a total of 100 wt % of the rare earth iron-based magnet powder and the polystyrene. A method for producing the rare earth iron-based ring magnet according to any one of claims 4 to 7.

Citation Information

Patent Citations

  • The permanent magnet and its manufacturing method

    JP1989000703A

  • Manufacture of rare earth-iron permanent magnet

    JP1990198104A

  • Manufacture of rare earth-iron based magnet

    JP1991284809A

  • Method for manufacturing sintered body for forming sintered magnet, and method for manufacturing permanent magnet using sintered body for forming sintered magnet

    WO2018056390A1